2013
DOI: 10.1002/adma.201303392
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Stable n‐Channel Organic Single Crystal Field‐Effect Transistors Based on Microribbons of Core‐Chlorinated Naphthalene Diimide

Abstract: Ribbon-shaped single crystal transistors based on naphthalene diimide Cl2-NDI exhibit excellent n-channel performance with the mobility as high as 8.6 cm(2) V(-1) s(-1) in air. The combination of ambient stability and high mobility n-channel transport closes the gap between p- and n-channel SCFETs and opens the door for the manufacture of high performance complementary organic circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
121
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(128 citation statements)
references
References 44 publications
2
121
1
4
Order By: Relevance
“…1d: 35 , thus yielding first evidence that a different crystallographic phase has been obtained by sublimation, as will be confirmed by the detailed comparison of their single-crystal structures below (Supplementary Data 1-3). In the following, we will denote this polymorph by b-phase, whereas the formerly described phase 35 with smaller layer spacing is called a-phase. Based on these new results, we can now also re-assign the hitherto reported vacuum-processed thin-film transistors 31 to relate to the b-phase molecular packing arrangement.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…1d: 35 , thus yielding first evidence that a different crystallographic phase has been obtained by sublimation, as will be confirmed by the detailed comparison of their single-crystal structures below (Supplementary Data 1-3). In the following, we will denote this polymorph by b-phase, whereas the formerly described phase 35 with smaller layer spacing is called a-phase. Based on these new results, we can now also re-assign the hitherto reported vacuum-processed thin-film transistors 31 to relate to the b-phase molecular packing arrangement.…”
Section: Resultsmentioning
confidence: 65%
“…Although our recently reported procedure towards high mobility SCFETs was based on ribbon-shaped crystals of Cl 2 -NDI grown by the drop-casting method on n-octadecyltriethoxysilane (OTES)-modified substrate and by solvent evaporation method ( Supplementary Fig. 1) 35 , the low molecular weight of Cl 2 -NDI (M ¼ 699 g mol À 1 ) and excellent air-stability suggested that this…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dichlorinated NDI based molecular semiconductors 1l and 1m with different fluoroalkyl chains show identical LUMO energy levels of À4.01 eV. 139,147 Compound 1l exhibits electron mobilities of 0. 86 ) when the device is stored in air for 82 days.…”
mentioning
confidence: 99%